Patient‐level meta‐analysis of the EDITION 1, 2 and 3 studies: glycaemic control and hypoglycaemia with new insulin glargine 300 U/ml versus glargine 100 U/ml in people with type 2 diabetes. Issue 9 (16th June 2015) - Ritzel, R.; Roussel, R.; Bolli, G. B.; Vinet, L.; Brulle‐Wohlhueter, C.; Glezer, S.; Yki‐Järvinen, H.
<x xml:space="preserve">Abstract</x> Aims To conduct a patient‐level meta‐analysis of the EDITION 1, 2 and 3 studies, which compared the efficacy and safety of new insulin glargine 300 U/ml (Gla‐300) with insulin glargine 100 U/ml (Gla‐100) in people with type 2 diabetes (T2DM) on basal and mealtime insulin, basal insulin and oral antihyperglycaemic drugs, or no prior insulin, respectively. Methods The EDITION studies were multicentre, randomized, open‐label, parallel‐group, phase IIIa studies, with similar designs and endpoints. A patient‐level meta‐analysis of the studies enabled these endpoints to be examined over 6 months in a large population with T2DM (Gla‐300, n = 1247; Gla‐100, n = 1249). Results No significant study‐by‐treatment interactions across studies were found, enabling them to be pooled. The mean change in glycated haemoglobin was comparable for Gla‐300 and Gla‐100 [each −1.02 (standard error 0.03)%; least squares (LS) mean difference 0.00 (95% confidence interval (CI) −0.08 to 0.07)%]. Annualized rates of confirmed (≤3.9 mmol/l) or severe hypoglycaemia were lower with Gla‐300 than with Gla‐100 during the night (31% difference in rate ratio over 6 months) and at any time (24 h, 14% difference). Consistent reductions were observed in percentage of participants with ≥1 hypoglycaemic event. Severe hypoglycaemia at any time (24 h) was rare (Gla‐300: 2.3%; Gla‐100: 2.6%). Weight gain was low (<1 kg) in both groups, with less gain with Gla‐300 [LS mean difference −0.28 kg (95% CI −0.55 to −0.01); p = 0.039]. Both treatments were well tolerated, with similar rates of adverse events. Conclusion Gla‐300 provides comparable glycaemic control to Gla‐100 in a large population with a broad clinical spectrum of T2DM, with consistently less hypoglycaemia at any time of day and less nocturnal hypoglycaemia.